Immune checkpoint regulation is critically involved in canine cutaneous histiocytoma regression - Diehl, Benjamin; Hansmann, Florian (Frontiers in Veterinary Science, 2024)
Introduction: Canine cutaneous histiocytoma (CCH) is a benign tumor frequently occurring in young dogs which is derived from Langerhans cells (LC). Distinguishing features of this tumor are its spontaneous regression following a rapid tumor growth. Impaired control of immune checkpoints during tumor development and progression is a widespread phenomenon which may result in an absent or ineffective immune response. The interaction between the inflammatory response and the expression of immune checkpoint molecules is only partially described in this tumor type. The aim of this study was to identify immune checkpoint molecules and molecules from the interferon-mediated immune response that are involved in the regression of CCH. Methods: Forty-eight CCH derived from dogs ≤ 4 years of age were assigned to one of four groups according to the severity and distribution of lymphocyte infiltration. Using immunohistochemistry and whole-slide image scans of consecutive sections the expression of programmed death protein ligand 1 (PD-L1), CD80, CD86, Survivin, forkhead box protein 3, Ki-67, cleaved caspase-3, CD3 and mx1 were investigated. RNA in-situ hybridization was performed for transcripts of mx1 and interferon-γ Results: Neoplastic cells showed an expression of PD-L1, CD80, CD86 and Survivin. The density of CD80 expressing cells was negatively correlated with regression while the density of cleaved caspase-3 positive cells increased with regression. Mx1 transcripts and protein were predominantly localized in neoplastic cells while interferon-γ transcripts were most frequently detected in T-cells. Conclusions: The expression of the immune checkpoint molecules CD86 and PD-L1 and particularly the reduced expression of CD80 in groups 3 and 4 indicate an influence of the investigated immune checkpoints on tumor regression. In parallel an activation of the apoptotic cascade during regression is suggested. Finally, the detection of mx1 within the neoplasm pinpoints to a yet undisclosed role of anti-cellular signaling in tumor immunity.